Exploring antecedents and outcomes of burnout among emergency department staff using the job demands-resources model: A scoping review protocol - Yang, Luhuan; Lei, Yunhong; Chu, Dongmei; Jiang, Jiawei; Li, Zifeng; Tang, Yanhua; Abd Rahman, Anita (Public Library of Science, 2024)
Introduction High levels of burnout are prevalent among Emergency Department staff due to chronic exposure to job stress. There is a lack of knowledge about anteceding factors and outcomes of burnout in this population. Aims To provide a comprehensive overview of burnout and identify its workplace antecedents and outcomes among Emergency Department staff. Methods The scoping study will follow the methodology outlined by the Joanna Briggs Institute. PubMed, Scopus, Web of Science, APA PsycInfo, and CINAHL databases will be searched using predefined strategies. Two reviewers will screen the title, abstract and full text separately based on the eligibility criteria. Data will be charted, coded, and narratively synthesized based on the job demands-resources model. Conclusion The results will provide insights into the underlying work-related factors contributing to burnout and its implications for individuals, healthcare organizations, and patient care. © 2024 Yang et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.